Assessment of interalveolar height deficiency using computed tomography in patients with TMJ dysfunction in articulation-occlusion disorders - Proschenko, Andriy (ScienceRise: Medical Science, 2024)
This article reviews the assessment of interalveolar height deficit in morphometric comparison with its projection onto the superior space of the temporomandibular joint (TMJ) using cone-beam computed tomography (CT) of the TMJ. The technique for calculating the gaps between the fossa and the head, determining the coefficients for their comparison, and their correlation with clinical signs of TMJ dysfunction in occlusal and articulatory disorders is described. The aim - to determine CT diagnostic criteria for decreased interalveolar height in patients with functional TMJ disorders with occlusal and articulatory disorders at the stage of orthopedic treatment planning. Materials and research methods. An examination was conducted of 150 patients with functional disorders of the chewing apparatus and occlusal disorders, who were included in the experimental group and 30 practically healthy individuals - the control group. Both groups were comparable in age and sex. Cone-beam tomography was performed on the MyRay Hyperion X9 PRO model with iRYS 16.3.1 software. During the clinical dental examination, the occlusion of the dentition was assessed, the reduction of the interalveolar height was determined, the width of the mouth opening was assessed, the mobility of the lower jaw was assessed, the symmetry of the mouth opening was determined, clicking and crunching in the TMJ were determined. Research result. When analyzing cone-beam tomography data, interalveolar height deficiency was classified as a decrease in the proposed coefficient for assessing the size of the upper TMJ space in at least one joint. A decrease in the specified ratio was found in 130 (86.67 %) patients with TMJ dysfunction and occlusal and articulation disorders according to CT data and confirmed by the anatomical and physiological method in 81 (54.00 %) patients, while its moderate decrease was confirmed by measurements by the topographic and physiological method (0.5-2.5 mm) in 62 (76.54 %) people and a significant decrease (more than 2.5 mm) in 19 (23.46 %) people, in 20 (13.33 %) patients, the coincidence of the absence of interalveolar height deficiency according to CT data and the anatomical and physiological method was noted. Bilateral reduction of interalveolar height was found in 82 (54.67 %) patients of the study group; 36 (24.00 %) of them had clinically observed pain syndrome. When assessing the deficiency of interalveolar height by the topographic-physiological method, confirmation of its moderate reduction (0.5-2.5 mm) was found in 51 (62.20 %) individuals and a significant reduction (more than 2.5 mm) in 8 (9.75 %) individuals. Unilateral reduction of interalveolar height was found in 48 (32.00 %) patients of the study group; 20 (41.66 %) of them had clinically observed pain syndrome. Conclusions. The assessment of the size of the superior articular space in comparison with the average value of the anterior and posterior articular gaps when determining their sizes using cone-beam CT of the TMJ may be a marker of decreased interalveolar height in patients with TMJ dysfunction and occlusal and articulatory disorders